2017
DOI: 10.3991/ijes.v5i1.6494
|View full text |Cite
|
Sign up to set email alerts
|

Which Mobile Learning is More Suitable on Physics Learning in Indonesian High School?

Abstract: Abstract-The use of mobile learning tool has controversy in Indonesian schools. Some teachers feel that it would interfere with the learning process in the classroom, but at the same time teachers saw a lot of potential of mobile technology. The goal of this study is to observe secondary schools on facilitating students through the use of mobile learning. This research is descriptive qualitative evaluations on the assembling mobile learning in several secondary schools in several regions in Indonesia during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Along with the development of technology, turns the computer as a medium of learning has a drawback that is affecting students in using it. This is spelled out by [14], who said that mobile Internet usage in 2015 Increased by 28% in Indonesia, the which meant A relatively large shift from the use of laptops to mobile devices. Computers, laptops even though, less practical as modern learning media that needs to be revisited to obtain the appropriate modern learning media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the development of technology, turns the computer as a medium of learning has a drawback that is affecting students in using it. This is spelled out by [14], who said that mobile Internet usage in 2015 Increased by 28% in Indonesia, the which meant A relatively large shift from the use of laptops to mobile devices. Computers, laptops even though, less practical as modern learning media that needs to be revisited to obtain the appropriate modern learning media.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reasons explained by the teacher in using mobile learning in schools namely 1) the need for time-learning flexibility; 2) giving students the opportunity to repeat the material indefinitely; 3) learning resources that are side by side for students [14]. The results reveal that learning habits and continuous learning are influenced by the perceptions of students' mobile learning, where good perceptions will help students understand the usefulness of mobile learning so that more students are accustomed to using mobile learning, fewer doubts about using it in the that a sustainable future learning will be improved [19].…”
Section: Introductionmentioning
confidence: 99%
“…These rapid technological developments, on the other hand, have a disastrous impact on students. They become less focused on the lessons because they play more with their mobile phone during the experience, and in worse conditions, students decrease their ability to interact and work with friends and teachers directly (Sulisworo, Yunita, & Komalasari, 2017). Collaborative learning can be used by combining collaborative tools to prevent the worse things.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the implementation of the strategy is fit to the level of mastery of IT of the teachers and students. The results of the research before showed that from various existing LMS (for example Moodle, Google Classroom, and Socrative), the LMS that was relatively appropriate for teachers in Indonesia was Edmodo [21], [22]. Features with a simple one are the advantages of this LMS.…”
Section: Introductionmentioning
confidence: 99%